Species diversity and abundance of parasitoids of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) from South Sumatra, Indonesia - SITI HERLINDA; SUWANDI SUWANDI; CHANDRA IRSAN; RIAN ADRIAN; FAIRUZ FAWWAZI; FAIZ AKBAR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Herlinda S, Suwandi S, Irsan C, Adrian R, Fawwazi F, Akbar F. 2023. Species diversity and abundance of parasitoids of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) from South Sumatra, Indonesia. Biodiversitas 24: 6184-6190. The parasitoid species attacking Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) have never been reported from South Sumatra. The objectives of this research were to identify and analyze the species diversity of egg and larval parasitoids of S. frugiperda and to determine their abundance in corn fields from South Sumatra. Surveys were carried out in Ogan Komering Ilir District, Ogan Ilir District, Muara Enim District, and Palembang City. The results showed that fourteen species of parasitoids were found attacking eggs and larvae of S. frugiperda in South Sumatra. Two species were egg parasitoids (Telenomus remus (Nixon) and Trichogramma sp.), and 12 species of larval parasitoids (Chelonus formosanus Sonan, Chelonus oculator F., Chelonus annulipes Wesm., Chelonus cautus (Cresson), Microplitis manilae Ashmead, Microplitis marshallii Kokujev, Euplectrus corriemoreauae Hansson, Compsilura concinnata (Meigen), Sarcophaga sp., Macrocentrus sp., Exorista sp., and Megaselia sp.). The most abundant species of the parasitoids found was T. remus. The highest species diversity was found in Muara Enim District. The number of parasitoid species was greater in the dry season compared to the rainy season. Egg parasitism rates were significantly higher at the corn vegetative stage (59.03%) compared to the generative stage (53.56%).